Physicochemical Properties of Sago- and Corn Flour-Based Rice Analogues Fortified with Black-Eyed Bean Flour and Skimmed Milk Powder - Noer Abyor Handayani; Siswo Sumardiono; Aprilina Purbasari; Alfan Fatir Fatikah; Imam Muda Alhakim (Food Technology and Biotechnology)
Research background. With the increasing consumption of food commodities, particularly rice, and the substantial volume of food imports in Indonesia, there is an increasing need to explore alternative food sources. Rice analogues emerge as a potential substitute for traditional rice, serving as a viable staple food option. The aim of this study is to investigate the effect of the composition of raw material, namely sago and corn flour, on the physicochemical properties and consumer acceptance of rice analogues. Experimental approach. The rice analogues were produced using the hot extrusion method. The nutritional content (protein, carbohydrate, fat, moisture, fibre and ash) of the product was then analysed. Thermal stability and morphological properties were determined using differential scanning calorimetry (DSC) and scanning electron microscopy (SEM), respectively. A consumer acceptance test including taste, texture, aroma and colour was also carried out to evaluate the quality of cooked rice analogues. Results and conclusion. The results showed that the rice analogue produced by hot extrusion at 70 °C with black-eyed beans (15 % m/m) and skimmed milk powder (0.5 % m/m) had the most significant nutritional improvements such as increased content of protein, fat, carbohydrate, moisture content, ash and fibre. However, it should be noted that increasing the extrusion temperature above 70 °C meant that both density and hardness could no longer be controlled due to gelatinisation. Furthermore, 30 participants in the consumer acceptance test rated the texture, aroma, taste and colour positively, underlining the potential of rice analogue as a nutritious and attractive alternative to natural rice. The rice analogue made from modified sago with additional ingredients of corn and black-eyed beans has similar properties to natural rice. Novelty and scientific contribution. The combination of sago, corn and black-eyed bean flour as the main ingredients of the rice analogue is a novelty of this study. Furthermore, its nutritional profile exceeds that of natural rice, making it a viable and acceptable alternative in times of rice scarcity.